Restructuring sovereign debt : the case for ad hoc machinery - Rieffel, Lex (Brookings Institution Press, 2003)
"When developing countries began experiencing debt problems in the late 1960s, the Paris Club took shape as "ad hoc machinery" to restructure debt from export credit agencies. A decade later the London Club process emerged to handle workouts of commercial bank debt. Restructuring debt in the form of bonds became an issue in the late 1990s in Argentina and several other nations, and the International Monetary Fund recently proposed a permanent mechanism to deal with that challenge."